Perioperative brain injury marker concentrations in neonatal open-heart surgery: a prospective observational study - Jungner, Åsa; Lennartsson, Finn; Björkman-Burtscher, Isabella; Blennow, Kaj; Zetterberg, Henrik; Ley, David (Frontiers in Pediatrics, 2023)
Neonates with critical congenital heart defects undergoing open-heart surgery on cardiopulmonary bypass circulation are at risk for white matter brain injury. This article reports on pre- and postoperative plasma concentrations of brain injury markers glial fibrillary acidic protein (GFAP), neurofilament light (NfL) and Tau, and their respective associations with white matter lesions detected on postoperatively performed brain MRI. Forty term newborns with isolated critical congenital heart defects were included in a prospective observational study. Brain injury marker plasma concentrations were determined prior to surgery and at postoperative days 1, 2 and 3. Brain magnetic resonance imaging was performed pre- and postoperatively. Concentrations of brain injury markers were analysed using ultrasensitive single molecule array technology. Absolute pre- and postoperative plasma biomarker concentrations, and postoperative concentrations adjusted for preoperative concentrations were used for subsequent analysis. Plasma concentrations of GFAP, NfL and Tau displayed a well-defined temporal trajectory after neonatal cardiopulmonary bypass circulation. GFAP and Tau reached peak concentrations at postoperative day 2 (median concentrations 170.5 pg/mL and 67.2 pg/mL, respectively), whereas NfL continued to increase throughout the study period (median concentration at postoperative day 3 191.5 pg/mL). Adjusted Tau at postoperative day 2 was significantly higher in infants presenting with white matter lesions on postoperative MRI compared to infants without white matter injury.